Pancreatic Neuroendocrine Tumors: Update on the New World Health Organization Classification. Issue 5 (September 2017) - Klöppel, Günter; Klimstra, David S.; Hruban, Ralph H.; Adsay, Volkan; Capella, Carlo; Couvelard, Anne; Komminoth, Paul; La Rosa, Stefano; Ohike, Nobuyuki; Osamura, Robert Y.; Perren, Aurel; Scoazec, Jean-Yves; et al.
Abstract : Abstract: The first classification of the pancreatic neuroendocrine neoplasms (PanNENs) that characterized the individual tumor by criteria with prognostic significance appeared in 1995. These criteria included a distinction by site and size, by degree of histological differentiation (well vs poor), by function (with and without hormonal syndrome), by angioinvasion, and by metastatic spread. The subsequently developed World Health Organization classifications in 2000, 2004, and 2010 largely followed this concept, but added proliferative activity as the best criterion reflecting tumor growth. In 2010, the classification combined histological differentiation with stratification into 3 tiers of proliferative activity, mainly using Ki67 as the most reliable measure of proliferation. The predictive value of this classification and grading system that was soon accompanied by an adequate TNM staging system has proved to be so excellent that all major treatment options of PanNENs, as well as extrapancreatic NENs, have been currently based on this classification. The new World Health Organization 2017 classification is a refinement of the previous version. Its main change is the introduction of a "pancreatic neuroendocrine tumor grade 3" category to recognize grade-discordant pancreatic neuroendocrine tumors and distinguish them from pancreatic neuroendocrine carcinomas, which are defined by their poorly differentiated nature. There is increasing evidence that this phenotypical classification of PanNENs allows a targeted molecular analysis, which is going to broaden our understanding of the tumors' biology.